A baleful combination of trigeminal neuralgia and menopause: An epoch of cognizant - Vishal Mehrotra; Rohan Sachdev; Kriti Garg; Shubhra Saxena; Sheenam Sambyal (Wolters Kluwer Medknow Publications, 2021)
Introduction: Menopause is found to be associated with several adverse changes in the oro-facial complex, which may affect neural mechanisms because of attribution of the estrogen imbalance. Aim: The present study was conducted on female patients suffering from trigeminal neuralgia and was either in the peri-menopausal or menopausal age groups. The aim of the present study was to find out the incidence of trigeminal neuralgia in peri-menopausal and menopausal females. Material and Methods: In 2 years period, a total of 169 women patients with clinically diagnosed trigeminal neuralgia were included in the study. Based on neuralgic symptoms and gynecologist confirmation, selected patients were subdivided into groups based on age which were further subdivided into perimenopause and menopause. Collected data was tabulated and calculations were made with SPSS v21 and Chi-square test. Results: In the present study, 70.4% of patients were of 46-55 years of age which was the maximum proportion. Trigeminal neuralgia was more common in the age group of 46-55 years (82.2%), and the incidence of neuralgic pain was more common in the lower jaws (75.1%) and the right side of the face. In the present study, the lower jaw (79.8) was commonly involved as compared to the upper jaws in both perimenopausal (67.2%) and menopausal women (85.9%). Conclusion: This study stated that trigeminal neuralgia affects more commonly the older age group with a high incidence in postmenopausal women as compared to the perimenopausal women, where the lower jaw is more commonly affected in older and postmenopausal females.